1973
DOI: 10.2134/jeq1973.00472425000200030024x
|View full text |Cite
|
Sign up to set email alerts
|

Termination of Late Season Cotton Fruiting with Growth Regulators as an Insect‐Control Technique

Abstract: A technique is proposed for reducing the number of overwintering pink bollworms [Pectinophora gossypiella (Saunders)] by reducing their food supply late in the year. This is done by using growth regulators that prevent formation of new cotton (Gossypium sp.) bolls late in the season, but do not affect development of existing bolls or vegetation. Since most of the late‐season bolls do not mature, the effect on lint yield would be minimal.Three chemicals, (2‐chloroethyl) trimethyl ammonium chloride, (CCC); dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…This means as indicated in Tables (3 and 4), Ethephon ® treatment gave the highest reduction percentages, 56.68 and 37.60% of PBW infestation with 3 cm 3 /L, while, they were 50.66 and 43.75% of SBW infestation with 1.5 and 3.0 cm3/L in the first and second season, respectively. Results are confirmed with those obtained by Kittock et al (1973) who mentioned that they found 87 to 96% reduction in diapausing PBW larvae as they sprayed Ethephone on cotton late in August and early in September. In addition, in Arizona, USA, late season applications to cotton reduce late season fruiting forms as a source of host material for development of diapause PBW larvae (Bariola et al, 1990).…”
Section: -Efficacy Of Ethephon Treatment On Bollworms Infestationsupporting
confidence: 90%
See 1 more Smart Citation
“…This means as indicated in Tables (3 and 4), Ethephon ® treatment gave the highest reduction percentages, 56.68 and 37.60% of PBW infestation with 3 cm 3 /L, while, they were 50.66 and 43.75% of SBW infestation with 1.5 and 3.0 cm3/L in the first and second season, respectively. Results are confirmed with those obtained by Kittock et al (1973) who mentioned that they found 87 to 96% reduction in diapausing PBW larvae as they sprayed Ethephone on cotton late in August and early in September. In addition, in Arizona, USA, late season applications to cotton reduce late season fruiting forms as a source of host material for development of diapause PBW larvae (Bariola et al, 1990).…”
Section: -Efficacy Of Ethephon Treatment On Bollworms Infestationsupporting
confidence: 90%
“…Ethephon is a plant growth regulator which registered for use on cotton to accelerate mature boll opening (Henneberry et al, 1992). In addition, Ethephon reduced the number of green bolls remaining after harvest and reduction percentages of diaphausing pink boliworm larvae (Kittock et al, 1973). Before applying plant growth regulators., variety, soil type, fertility, irrigation potential and field history must be taken into consideration (Wilson, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Diapausing larvae overwinter in immature cotton bolls, trash, and soil (Bariola 1984). The removal of late-season immature cotton bolls is a viable option to reduce the overwintering population (Kittock et al 1973). Cultural control techniques that include shredding stalks, disking, plowing, and winter irrigation have been shown to result in high levels of mortality of diapausing larvae in bolls, trash, and soil (Watson 1980).…”
Section: Bt Transgenic Cotton -mentioning
confidence: 99%
“…Conversely, 2,4-D diethylamine applied to late season cotton (Gossypium spp. L.) reduced the number of green bolls remaining after harvest by more than 90%, thus causing 87 and 96% reductions in overwintering pink bollworm [Pectinophora gossypiella (Saunders)] (Lepidoptera: Gelechiidae) populations (26). Herbicide effects on food quality for insects.…”
Section: Introductionmentioning
confidence: 99%